1990
DOI: 10.1177/030089169007600307
|View full text |Cite
|
Sign up to set email alerts
|

External Radiotherapy in the Treatment of Tonsillar Carcinomas. Analysis of 183 Cases

Abstract: A retrospective analysis of 183 consecutive patients with tonsillar carcinoma obserevd from 1970 through 1984 and treated by external radiotherapy was carried out. The data were analyzed retrospectively to determine the factors affecting prognosis. Tumor size (T) and lymph node involvement (N) were found to be predominant prognostic factors. The difference in 5 year survival rate between T2 and T3 tumors was significant, and that between N1 and N3 was highly significant, whereas difference in survival could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the literature, the predictive value of the 7th edition of the TNM classification for oropharyngeal carcinomas, and for N classification in particular, has shifted over time as a consequence of the epidemic of HPV‐associated HNSCCs 13–34 . This shift prompted the publication of a new edition of the UICC staging system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the predictive value of the 7th edition of the TNM classification for oropharyngeal carcinomas, and for N classification in particular, has shifted over time as a consequence of the epidemic of HPV‐associated HNSCCs 13–34 . This shift prompted the publication of a new edition of the UICC staging system.…”
Section: Discussionmentioning
confidence: 99%
“…We found 10 studies published prior to 1990 all reporting N classification to be of prognostic importance (although only 2 studies provided results based on statistical analysis), while only 4 out of 12 studies published from 1990 onwards showed N classification to be of prognostic relevance (see Table 1). 13–34 In a previous study we tested the prognostic value of N classification in a group of 81 HPV‐positive and HPV‐negative TSCCs and found a decrease in prognostic value of N classification in the whole group 35 . N classification was of prognostic relevance only when tonsillar tumors were not HPV‐associated.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate radiotherapy achieves local control in approximately 60% to 80'% of T ? tumors and 40'K to 60% of T3 tumors (82,(90)(91)(92)(93)(94)(95). and surgery is reserved for recurrence.…”
Section: Moderate Turnors (7'2 Trritl 7'3)mentioning
confidence: 99%